Brand Image and Price: Influencing Smartfren Data Quota Purchasing Decisions: Gambaran Merek dan Harga: Pengaruh pada Keputusan Pembelian Kuota Data Smartfren - Ainur Rofiq; Ainur Rochmaniah (Academia Open, 2023)
This quantitative study examines the influence of brand image and price on purchasing decisions for Smartfren data quotas at the Renny Cell Waru counter. The research employed a total sampling technique, with 103 respondents completing questionnaires. Multiple linear regression analysis using IBM SPSS version 24 was conducted to analyze the data. The findings reveal that both brand image and price significantly affect purchasing decisions, with brand image exerting the strongest influence. This study contributes to the understanding of consumer behavior and provides valuable implications for marketers in the telecommunications industry. Highlights: Brand Image significantly impacts purchasing decisions for Smartfren data quotas. Price plays a significant role in shaping consumer decisions regarding Smartfren data quotas. Brand Image emerges as the most influential factor influencing purchasing decisions. Keywords: Brand Image, Price, Purchasing Decisions, Smartfren Data Quotas, Consumer Behavior